Investigating the exogenous application of 5-Aminlevulinic acid to improve turfgrass (Lolium perenneL.) surfaces grown in shade - Turnbull, Andrew (2021)
The quality of turfgrass playing surfaces can be severely compromised when grown in the modern sports stadia environment. Shade from the large grandstands prevent direct sunlight from reaching most of the pitch and Grounds Managers are using lighting rigs to replace natural light. Other solutions are required to reduce the high energy costs of this equipment yet maintain the essential high quality of the playing surfaces. This study investigated the effect of exogenous applications of 100mg L-1e 5-Aminolevulinic acid (5-ALA) to turfgrass Lolium perenne L. grown in 100% daylight (Light) and 50% daylight (Shade). Two experiments were setup to investigate a number of parameters. Experient One consisted of turfgrass L. perenne grown in tubs containing a sand rootzone overlying gravel to replicate the modern sports pitch construction. Clippings were analysed for chlorophyll content (NDVI), % Dry Weigh and leaf nutrient content (mg kg-1). Experiment Two used the same rootzone and grass seed as in Experiment 1 but grown in 3 inch pots. Fluorescence parameters measurements concentrated on the effects of exogenous applications of 100mg L-1 on Photosystem II (PSII): Maximum Quantum Yield (Fv/Fm), Quantum Yield (ØPSII or Fq’/Fm’), and Non-Photochemical Quenching (NPQ). Exogenous applications of 100mg L-1 5-ALA resulted in significant increases in chlorophyll (NDVI) in treated plants compared the Control (non-treated) in both Light and Shade on Days 7 and 14 after treatment, and in Shade on Day 14 after treatment. % Dry Weight increased only on Day 7 after treatment in Treated Shade grown plants. There were significant differences of some nutrients due to 5-ALA treatments: Mg and Zn on Day 0 (4 hours) after treatment; Mn and Zn on Day 7 after treatment. There were some effects on fluorescence parameters, but significant differences were mainly attributed to whether the plants were grown in Light or Shade, not applications of 5-ALA.